Applying Circular Supply Chain Quality Management in the Production Process of Traditional Fish Sauce Villages in Nam Dinh (Case Study of Sa Chau Fish Sauce Village, Giao Chau Commune, Giao Thuy District, Nam Dinh Province) - Phuong Anh, Nguyen; Van Anh, Do Thi; Thi Mung, Vu (VNU Journal of Science: Policy and Management Studies, 2024)
Sa Chau village, Giao Chau commune, Giao Thuy district, Nam Dinh province is one of the famous craft villages with traditional fish sauce products that are popular with consumers. However, the production process still has many limitations in quality management and household owners' awareness of sustainable production and business, so the amount of waste and emissions has not been treated effectively, causing serious consequences to local life, society and environment. Meanwhile, the process of minimizing greenhouse gas emissions in the production process is one of the top priorities that greatly contributes to Vietnam's NetZero goal. The research aims to implement circular economy solutions through applying the model “Circular supply chain quality management - CSCQM”.  The goal of the model is to optimize production processes and quality management in the supply chain to create circulation and reuse of resources, contributing to the formation of a sustainable production and consumption system, reducing resource waste and environmental pollution, while increasing business value and community development. By applying the model CSCQM, Sa Chau fish sauce village can strengthen cooperation with stakeholders into a sustainable ecosystem and increase the value of traditional fish sauce products. Strengthening responsible production and business practices will contribute to implementing Vietnam's NetZero commitment.